Effect of CNT-COOH Addition on the Compressive Strength, Chloride Resistance, and Microstructure of Cement Mortar - Xiaofan Wang; Yao Shi; Xueyang Pei; Lipeng Cui; Hua Zhu (Advances in Materials Science and Engineering)
This work evaluated the effect of multiwalled carboxyl carbon nanotube (CNT-COOH), upon cement mortar. In order to obtain a homogeneous suspension, the CNT-COOH was dispersed in distilled water, and it then underwent an ultrasonication treatment. Samples of cement mortar were prepared with varying the additions of this suspension at 0.01%, 0.05%, and 0.10% by weight of the cement. These samples were tested in compression and for chloride migration in terms of diffusion coefficient. An increase in the CNT-COOH content led to an increase in the compressive strength. While there was an increase in the chloride diffusion coefficient up to 0.05% weight fraction, higher dosage led to a drop in the chloride diffusion coefficient with a further increase in the compressive strength. Using mercury intrusion porosimetry (MIP), it is shown that at a weight fraction of 0.10%, CNT-COOH effects a pore-size refinement by eliminating macropores (≥50 nm) and a 34% reduction in porosity. The (scanning electron microscopy) SEM and (X-ray diffraction) XRD analyses confirm that CNT-COOH leads to mature hydration products, nucleation effect, and a refined microstructure.